Pemberdayaan Masyarakat melalui Edukasi Cara Pembuatan Pangan Olahan yang Baik, Bahan Tambahan Pangan, dan Kemasan Pangan untuk Penguatan Jaminan Keamanan pada Pelaku UMKM Bidang Makanan di Balikpapan - Juni Ekowati; Rosita Handayani; Dewi Melani Hariyadi; Mohammad Rizki Fadhil Pratama; Putri Hamidah Khairunnisa; Melanny Ika Sulistyowaty; Rossa Auli Tasha; Imamatin Nufus Melania; Ersanda Nurma Praditapuspa; Muhamad Ilham Royyan Nafi’ (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Food safety is a complex issue that involves stakeholders in its handling. The point of food safety is growing widely and is becoming a concern in the community because it is related to the quality of consumers' good health and well-being. The community service activities based on quality education focused on Good Processed Food Manufacturing Practices (CPPOB), safe use of Food Additives (BTP), and consideration of packaging selection that ensures food safety. Education is carried out to increase the understanding of SMEs actors regarding regulations of CPPOB, the use of BTP, and provisions on Food Packaging. The education process is carried out online using the Zoom Meeting platform. Learning activity is carried out in one direction through lectures and questions and answers sessions. The increase in participants' understanding was measured by comparing the distribution of average scores, pretest, and post-test statistical tests. The effectiveness and quality of the educational process were measured using an evaluation questionnaire with predetermined indicators. The education carried out related to CPPOB, the use of BTP, and the selection of food packaging performed by the community service team of the Department of Pharmaceutical Sciences, Faculty of Pharmacy, Universitas Airlangga to SMEs in Balikpapan has proven to increase the understanding of business actors. It can fulfill their needs and target activity evaluation indicators that have been determined.